Deviating HER2 status between primary breast carcinomas and their liver metastases - Chen, Yuexia; Yang, Liu; Qu, Wei; Tu, Jianhong; Cheng, Suqing; Guo, Xingmei (Frontiers in Oncology, 2025)
BackgroundHER2 heterogeneity existed in metastatic breast cancer compared with primary breast cancer, and the differences may influence treatment decisions and prognosis for patients with metastatic breast cancer.MethodsTo investigate HER2 heterogeneity in primary breast lesions and liver metastases and its impact on prognosis.HER2 expression in 87 patients with breast cancer liver metastases was categorized into three groups using IHC or FISH: HER2-0, HER2 low expression, and HER2-positive. The chi-square test was used to evaluate the association between HER2 heterogeneity and clinicopathological characteristics, while prognosis was analyzed using Kaplan–Meier survival and COX regression analyses.ResultsHER2 heterogeneity was found in 38% of patients with primary breast cancer and liver metastases. Analysis of clinicopathological features showed that patients aged ≥ 50 years and those with high ER heterogeneity were more likely to display HER2 heterogeneity. Kaplan-Meier survival analysis showed no significant difference in OS or DFS between the HER2-low expression group and the HER2–0 groups, either in primary breast lesions or liver metastases. Similarly, no significant differences in OS or DFS were observed among patients aged ≥ 50 years. Notably, COX univariate and multivariate analyses identified heterogeneous PR expression as an independent risk factor for disease-free survival in this cohort of breast cancer patients.ConclusionsHER2 heterogeneity is present in both primary breast cancer and liver metastases. Ongoing monitoring of molecular markers, particularly HER2 expression, remains essential for breast cancer patients, as it may provide opportunities for therapeutic intervention.